Correlation between the internal quantum efficiency and photoluminescence lifetime of the near-band-edge emission in a ZnO single crystal grown by the hydrothermal method. (3rd December 2020) - Kojima, Kazunobu; Chichibu, Shigefusa F.
Abstract: The internal quantum efficiency (IQE) and photoluminescence lifetime τ PL of the near-band-edge emission in a ZnO single crystal grown by the hydrothermal method were measured by the omnidirectional photoluminescence and time-resolved photoluminescence spectroscopy, respectively. The IQE showed a monotonic increase when the cw photo pumping density exceeds 2.0 × 10 − 2 W cm −2, while a constant IQE was observed below that. By using the data set of IQE and τ PL measured under pulsed excitation conditions, radiative and nonradiative recombination lifetimes were separately quantified. Since a significant increase was observed for the nonradiative recombination lifetime, the origin of the IQE increase was revealed to be dominated by the saturation of nonradiative recombination centers.